2017
DOI: 10.1002/2017jc012945
|View full text |Cite
|
Sign up to set email alerts
|

Velocity and Drag Evolution From the Leading Edge of a Model Mangrove Forest

Abstract: An experimental study of unidirectional flow through a model mangrove forest measured both velocity and forces on individual trees. The individual trees were 1/12th scale models of mature Rhizophora, including 24 prop roots distributed in a three‐dimensional layout. Thirty‐two model trees were distributed in a staggered array producing a 2.5 m long forest. The velocity evolved from a boundary layer profile at the forest leading edge to a vertical profile determined by the vertical distribution of frontal area,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
77
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 39 publications
(51 reference statements)
9
77
2
Order By: Relevance
“…In general, velocity profiles, and hence turbulence, are strongly dependent both on the submergence depth and the nonuniformity of the canopy (Horstman et al, ; Liu et al, ). Recently, two laboratory studies investigated turbulence within modeled mangrove forests (Maza et al, ; X. Zhang et al, ). Both studies focused on Rhizophora mangroves with dense prop root structures, whose geometry differs substantially from the pneumatophores of the predominant Sonneratia mangroves considered in this paper.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, velocity profiles, and hence turbulence, are strongly dependent both on the submergence depth and the nonuniformity of the canopy (Horstman et al, ; Liu et al, ). Recently, two laboratory studies investigated turbulence within modeled mangrove forests (Maza et al, ; X. Zhang et al, ). Both studies focused on Rhizophora mangroves with dense prop root structures, whose geometry differs substantially from the pneumatophores of the predominant Sonneratia mangroves considered in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies focused on Rhizophora mangroves with dense prop root structures, whose geometry differs substantially from the pneumatophores of the predominant Sonneratia mangroves considered in this paper. Maza et al () and X. Zhang et al () observed two distinct zones of enhanced TKE: one near‐bed zone generated by stem and trunk wakes and another zone formed by velocity shear that was generated by the sharp decrease in vegetation density at the top of the prop roots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technical note provides a practical set-up to derive both time-varying and period-averaged vegetation drag coefficients (C D ) following the direct measuring method [36][37][38]. Different from previous studies, standard force sensors are applied to compose four synchronized force-velocity measuring systems in the current experiment.…”
Section: Discussionmentioning
confidence: 99%
“…It derives C D by calibrating its values to obtain the best fit between modelled and measured wave height evolution over vegetation fields. The direct measurement method is a new method, which has been developed since the 2010s [36][37][38]. This method directly applies the Morrison equation and measured in-phase force and velocity data to determine C D .…”
Section: Introductionmentioning
confidence: 99%